Potensi senyawa turunan flavonoid dalam menjadi inhibitor enzim HMG-Coa reductase kandidat obat h - I Putu Bayu Agus Saputra; I Putu Dedy Arjita (Jurnal Penelitian Pendidikan IPA, 2024)
Cardiovascular disease (CVD) is a disease that causes death in the world. Behavioral risk factors are crucial in dealing with CVD disease. High levels of cholesterol in the blood are associated with hypercholesterolemia. It can increase the risk of CVD disease. The HMG-CoA reductase enzyme is an enzyme that plays a role in cholesterol synthesis. It will convert the HMG-CoA compound into the mevalonate. Inhibition of this enzyme can reduce cholesterol synthesis because it inhibits the formation of mevalonate, which is the initial stage of cholesterol synthesis. Herbal compounds are compounds produced by plants. It has good benefits for the body. Flavonoid compounds can be beneficial for health. Molecular docking is a method used to determine the binding affinity and interaction values ​​of the enzyme protein interaction with the ligand to be bound. The results of Apigenin binding affinity values is -7.7 kcal/mol, Luteolin is -8 kcal/mol, Quercetin is -8.2 kcal/mol, Kaempferol is -7.4 kcal/mol, Phloretin is -6.8 kcal/mol, Chalconaringenin is -6.9 kcal/mol, Cyanidin is -7.9 kcal/mol, Delphinidin is -7.8 kcal/mol, Hesperetin is -7.7 kcal/mol, Narigenin is -7.8 kcal/mol, Daidzein is -6.8 kcal/mol, Genistein is -7 kcal/mol, Rutin is -9.2 kcal/mol, Taxifolin is -8 kcal /mol, Diosmetin is -7.6 kcal/mol, and its native ligand Rosuvastatin is -8.5 kcal/mol. Flavonoid derivative compounds can bind to the HMG-CoA reductase enzyme. They can be candidates for antihyperlipidemia drugs.